Remolding Water Content Effect on the Behavior of Frozen Clay Soils Subjected to Monotonic Triaxial Loading - Shuai Qi; Jinhui Liu; Wei Ma; Jing Wang; Houwang Bai; Shaojian Wang (Applied Sciences)
Understanding the mechanical behavior of frozen clay subgrade soils was essential for ensuring the safe and stable operation of transportation lines. However, the influence of remolding water content w on this behavior remained unclear. To address this gap, this study examined the effect of w through monotonic triaxial testing. Three typical remolding water contents (w = 19%, 27.5% and 35%) and three confining pressures (σ3 = 200 kPa, 700 kPa and 1200 kPa) were considered. Results showed that the mechanical behavior of frozen clay soils displayed a clear dependence on w, which was controlled by microstructural evolution. As w increased, the shear strength qmax, resilient modulus E0 and cohesion c increased, which resulted from the progressive development of ice bonding within the shear plane. A threshold w value was found at wopt = 27.5%, marking a structural transition and separating the variations of qmax, E0 and c into two regimes. When w ≤ 27.5%, the soil fabric was controlled by clay aggregates. As w increased, the growth in ice cementation was confined within these aggregates, leading to limited increase in qmax, E0 and c. However, as w exceeded 27.5%, the soil fabric transitioned into a homogeneous matrix of dispersed clay particles. In this case, increasing w greatly promoted the development of an interconnected ice cementation network, thus significantly facilitating the increase in qmax, E0 and c. The friction angle φ decreased with w increasing, primarily due to the lubrication effect caused by the growing ice. In addition, the enhanced lubrication effect in the clay particle-dominated fabric (w > 27.5%) resulted in a larger reduction rate of φ. Regarding Poisson’s ratio v and dilation angle ψ, the w increase led to growth in both parameters. This phenomenon could be explained by the increased involvement of solid ice into the soil structure.